Fritjhof Schuon's Contribution to the Development of Sufism in the West - Unsi Andal Bara (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This journal explores how the contributions of Frithjof Schuon, a philosopher and mystic, are known for his concept of transcendent unity that emphasises the core unity of all the world's great religious traditions. In his thought, Schuon integrated the teachings of Sufism, especially the concept of wahdat al-wujud (unity of existence), to show that behind the diversity of religions lies one and the same essential truth. Schuon viewed differences in rituals and doctrines as merely manifestations of one transcendent reality. His philosophical approach broadens the understanding of Sufism and shows that mystical experiences in different religious traditions lead individuals towards the same divine unity. The research in this journal is a desk research that focuses on library materials as primary and secondary documents with an analytical-descriptive approach.The results of this study show that Schuon's contribution to the development of Sufism is significant in expanding inter-religious dialogue and enriching Sufism literature. By pointing out the essential similarities between mystical experiences in Islam and other religions, Schuon helped to strengthen inter-religious understanding. His works provided a broader and deeper theoretical framework for studying Sufism, as well as making it more accessible to a wider audience. Schuon's views remain relevant in the study of comparative religion and contemporary spirituality, offering insights into the essential unity of mystical experience across different religious traditions.